Adsorption of the 2,4-Dichlorophenoxyacetic Acid Dimethylamine by Raw and Modified Bentonite - Yonten, Vahap; Kubilay, Senol; Battal, Peyami (Asian Journal of Chemistry, 2011)
The adsorption of the 2,4-dichlorophenoxyacetic acid dimethyl amine on raw bentonite (Tokat, Turkey), modified bentonite with base and modified bentonite with acid has been studied using high pressure liquid chromatography (HPLC) and FT- infrared spectrophotometer. Sorption of 2,4-dichlorophenoxyacetic acid dimethyl amine on raw bentonite, modified bentonite with base and modified bentonite with acid was compared solving in different solutions such as aqueous and aqueous-ethanol solutions based on adsorption isotherms. The effect of temperature, time and pH were observed on adsorption of 2,4-dichlorophenoxyacetic acid dimethyl amine. Sorption mechanisms in soils, the effect of surface functional groups as well as parameters influencing adsorption were discussed. Then maximum adsorption of 2,4-dichlorophenoxyacetic acid dimethyl amine capacity was measured on modified bentonite with base in pH 5 at 40 ºC for 24 h. The modified bentonite with base used in experimental work played a major role than on the adsorption of 2,4-dichlorophenoxyacetic acid dimethyl amine so, the modified bentonite with base has better characteristics than raw bentonite and modified bentonite with acid adsorbents. The Freundlich isotherms of aqueous-ethanol solution was better than isotherms of aqueous solution for much better to adsorb of 2,4-dichlorophenoxyacetic acid dimethyl amine.